Does retrenchment strategy induce family firm's value? A study from Malaysia - Ung, Likjing; Brahmana, Rayenda Khresna; Puah, Chin Hong (Inderscience Enterprises Ltd., 2016)
This paper investigated the performance of retrenchment strategy of Malaysian family firms. It followed prior research in value of diversification strategy such Lins and Servaes (2002), Fauver et al. (2004), or Lee et al. (2012), but with different strategy perspective which was retrenchment strategy. We also followed Reebs (2003) research on the performance family firms but taking Malaysia as the background of study. In short, we investigated the relationship between retrenchment and performance works in Malaysia family firms. We considered a sample of 443 Malaysia listed family companies between 2004 and 2013. Our background of study was Malaysian market, which was dominated by family firms. We documented the resulting strategy of retrenchment in family-controlled firm, which led to positive effect on financial performance and negative effect on accounting performance